Visualizing Variability: The Impact of Dynamic Geometry on the Development of Algebraic Thinking and the Learning of Linear Functions - Paulo Vitor da Silva Santiago; Francisco Cleuton de Araújo; Antônio Hugo Da Silva Geraldo (CV. Edutechnium Indonesia, 2026)
Proficiency in interpreting mathematical functions is fundamental to academic success in the 21st century; however, many students face significant obstacles in translating abstract concepts into real graphical representations. This research addresses the need for innovative methodologies when implementing the use of GeoGebra software as a mediating tool to enhance comprehension skills related to linear functions. The study employed a Research and Development approach based on a qualitative case study model, involving stages of diagnosis, technological intervention, and pedagogical evaluation. Participants included high school students who interacted with the software and provided data through questionnaires, participant observation, and analysis of practical activities. The results indicated that the use of GeoGebra is highly dynamic, with student acceptance levels exceeding 90%. Furthermore, the visual perception of the growth and decay properties of functions showed a notable qualitative improvement after digital manipulation. In conclusion, GeoGebra effectively enhances the understanding of functions and offers a dynamic alternative to traditional mathematical instruction. The impact of this research lies in providing educators with an interactive resource capable of stimulating geometric intuition and optimizing learning outcomes in mathematics.